Palaeozoic-Recent geological development and uplift of the Amanos Mountains (S Turkey) in the critically located northwesternmost corner of the Arabian continent. Issue 1 (1st January 2017) - Duman, Tamer Y.; Robertson, Alastair H. F.; Elmacı, Hasan; Kara, Meryem
Abstract: We have carried out a several-year-long study of the Amanos Mountains, on the basis of which we present new sedimentary and structural evidence, which we combine with existing data, to produce the first comprehensive synthesis in the regional geological setting. The ca. N-S-trending Amanos Mountains are located at the northwesternmost edge of the Arabian plate, near the intersection of the African and Eurasian plates. Mixed siliciclastic-carbonate sediments accumulated on the north-Gondwana margin during the Palaeozoic. Triassic rift-related sedimentation was followed by platform carbonate deposition during Jurassic-Cretaceous. Late Cretaceous was characterised by platform collapse and southward emplacement of melanges and a supra-subduction zone ophiolite. Latest Cretaceous transgressive shallow-water carbonates gave way to deeper-water deposits during Palaeocene-Eocene. Eocene southward compression, reflecting initial collision, resulted in open folding, reverse faulting and duplexing. Fluvial, lagoonal and shallow-marine carbonates accumulated during Late Oligocene(?)-Early Miocene, associated with basaltic magmatism. Intensifying collision during Mid-Miocene initiated a foreland basin that then infilled with deep-water siliciclastic gravity flows. Late Miocene-Early Pliocene compression created mountain-sized folds and thrusts, verging E in the north but SE in the south. The resulting surface uplift triggered deposition of huge alluvial outwash fans in the west. Smaller alluvial fans formed along both mountain flanks during the Pleistocene after major surface uplift ended. Pliocene-Pleistocene alluvium was tilted towards the mountain front in the west. Strike-slip/transtension along the East Anatolian Transform Fault and localised sub-horizontal Quaternary basaltic volcanism in the region reflect regional transtension during Late Pliocene-Pleistocene (<4 Ma).